Underground Neighbors: Shared Root-Associated Fungi Facilitating the Coexistence of Nothofagus obliqua and Pinus ponderosa - Fioroni, Facundo; Carron, Ayelen Inés; Soto Mancilla, Matias A.; Pastorino, Mario Juan; Fernandez, Natalia Veronica (Springer, 2025)
Despite the environmental and economic advantages of mixed plantations over monospecific ones, their implementation remains limited due to a lack of comprehensive understanding. Soil microorganisms, particularly root-associated fungi, have the potential to enhance plant fitness. In this study, we examined the effects of soil origin (native forest/pine plantation), cultivation type (monospecific/mixed), and the application of a commercial ectomycorrhizal inoculant on the growth and root-associated fungi (ectomycorrhizal fungi -EcMF- and root endophytic fungi -REF-) in seedlings of two important forestry species, Nothofagus obliqua (native) and Pinus ponderosa (non-native). Both species showed greater growth in forest soil, likely due to its higher nutrient content. In the plantation soil, seedlings in mixed cultures outperformed those in monospecific ones. The commercial inoculant had a positive effect on P. ponderosa but a negative impact on N. obliqua. Each forestry species had greater ectomycorrhizal abundance in their respective soil of origin, but EcMF richness and diversity were higher in the plantation soil. REF were more abundant in plantation soil. Notably, some EcMF demonstrated growth-promoting capabilities. Our findings highlight the potential of co-cultivating N. obliqua and P. ponderosa, whether for commercial or ecological restoration purposes, and underscore the importance of considering root associated fungi during the process.